Peranan Badan Usaha Milik Desa Di Masa Pandemic Covid-19 Dalam Upaya Meningkatkan Perekonomian Masyarakat Di Desa Sukalaksana Kabupaten Garut (Kajian Hukum Ekonomi Syariah) - Gausian, Gini; Abu Bakar, Azmi Al-Atiq (STAI Al Musaddadiyah Garut, 2022)
The welfare of society is crucial in efforts towards community development and empowerment. Government policies, through the establishment of Village-Owned Enterprises (BUMDes), aim to enhance the welfare of rural communities in the economic sector by harnessing local potentials. The purpose of this research is to determine the role of Village-Owned Enterprises in improving the community's economy during the Covid-19 pandemic in Sukalaksana Village based on Islamic economics. The method used to analyze the data in this research is qualitative descriptive with data collection from informants through observation and interviews. Based on the analysis, it is observed that there has been an increase in the income of the community after collaborating with the Sukalaksana Village-Owned Enterprise (BUMDes Binalaksana), and some members of the Sukalaksana Village community affected by the Covid-19 pandemic have been channeled by the village government to work in BUMDes Binalaksana in an effort to reduce unemployment during the Covid-19 pandemic. According to the study of Shariah economic law, the role of the Village-Owned Enterprise in Sukalaksana Village is in line with Islamic values, as seen from the main goal of the establishment of BUMDes Binalaksana to improve the welfare of the community and assist those in need of financial assistance, as well as the motto applied,